Direct Oral Anticoagulants Compared to Warfarin in Patients with Intermediate‐ to High‐Risk Pulmonary Embolism: A Systematic Review and Meta‐Analysis - Mohamed Nabil Elshafei; Muhammad Salem; Mutasem Almistarihi; Haider Alabd; Ahmed Khalil; Mohammed Danjuma (eJHaem)
ABSTRACT Introduction Despite recent advances in clinical therapeutics in patients with venous thromboembolism, uncertainty remains regarding the optimal anticoagulation strategy in patients with intermediate‐ to high‐risk pulmonary embolism. We aimed to evaluate the direct oral anticoagulants’ effectiveness and safety compared to warfarin in patients with intermediate‐ and high‐risk pulmonary embolism. Methods In this meta‐analysis, we systematically searched databases PubMed, EMBASE, Web of Science, and the Cochrane Library from their inception to April 30, 2024, for eligible studies that satisfy inclusion criteria. We included both randomized clinical trials and observational studies reporting on patients diagnosed with intermediate‐risk or high‐risk pulmonary embolism who were prescribed warfarin or direct oral anticoagulants (dabigatran, rivaroxaban, apixaban, or edoxaban). Two independent reviewers extracted relevant data from included studies based on the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guideline. Pooled odds ratios were derived from the included studies using the random‐effects model. The primary outcomes were the rate of venous thromboembolism recurrence and all‐cause mortality. Secondary outcomes were major and minor bleeding. Results Six studies, five observational and one randomized (n = 553 patients, out of which 45.7% received advanced therapy), were included in our meta‐analysis. Direct oral anticoagulants were associated with comparable recurrence and mortality rates versus warfarin (odds ratio [OR] 0.72, 95% confidence interval [CI] 0.15–3.43) and (OR 0.57, 95% CI 0.16–2.01), respectively. There was no significant difference in the safety outcomes (major and minor bleeding events), with a trend towards a decreased risk among direct oral anticoagulant treated cohorts (OR 0.3, 95% CI 0.08–1.1) and (OR 0.64, 95% CI 0.24–1.7), respectively. Conclusion In patients with intermediate‐ to high‐risk pulmonary embolism, with or without advanced therapy use, stabilized on direct oral anticoagulants, efficacy and safety outcomes were comparable to those on warfarin, with a trend towards less risk of major and minor bleeding events. Trial registration International PROSPERO database number: CRD42024499532